The Effect of Rice Field Management with Rotation The Impact of Rice and Secondary Crops on Farmers' Income in Nagori Pematang Gajing - Linda Reni P; Martua Siadari; Jhonson A Marbun; Adetya Ivanka (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to (1) determine the intensity index of rice and carp farming (IIP). (2) determine the income of rice and carp farmers in Nagori Pematang Gajing, Gunung Malela District. (3) determine the effect of cropping pattern index, fish production costs, paddy production costs, and farmer experience on farm income.This research was conducted in Pematang Gajing Village, Gunung Malela District, Simalungun Regency, North Sumatra Province. The research method used in this study was quantitative descriptive. The sampling method used was purposive sampling of 30 people. Data collection techniques used were observation, interviews, documentation, and questionnaires. Data analysis techniques used were planting intensity index analysis, income analysis, and multiple linear regression analysis. The results of the study show that (1). Rice farming and carp farming are carried out by farmers with an average age of 50 years. The average level of education is at the junior high school level. The average farmer's experience is 21 years. The average number of farmer family members is 4 people. The results of this study indicate that the largest rice production and carp farming are from rice production with an average R/C value of 3. While from carp farming with an average R/C value of 1.From the results of the determination test analysis (R2) it can be seen that variables X1, X2, X3, X4 can explain 60.4%, it is concluded that the difference of 39.6 is influenced by factors not included in the study. From the results of the simultaneous test analysis (F test) X1, X2, X3, X4 have a significant effect on (Y). with a sig value of 0.00 <0.05. From the results of the partial test analysis (t test) X1, X3, X4 have a significant effect on (Y), while X2 is not significant on the increase in (Y).